Examining the Impact of Information Disclosure Quality and Conservatism on Accounting Information of Companies Listed on the Tehran Stock Exchange - Khanagha, Jamal Barzegari; Parvare, Tahere (International Journal of Economics and Financial Issues, 2017)
Regarding the expansion of economic activities, today,development of financial markets and stimulation of investment in capital markets, especially in Stock Exchange by natural and legal persons,are the most important tools to make the right decisions and gain expected and optimum use of financial resources, access to accurate information, timely, accurate, and realistic analysis of information. Besides, it is expected that in efficient capital markets,all the available information is quickly reflected in the prices of securities.The aim of this study is to investigate the role of financial information disclosure quality, conservative company management, andtheir mutual impact on the relevance of accounting information.As in previous studies, the impact of systematic risk (beta) and the ratio of book value to market value on the relevance of accounting information have been approved, in this study, each of these variables are considered as control variables of the model and their impact on the relevance of accounting information will be controlled. The statistical population of this study consisted of 101 companies listed on Tehran Stock Exchange during the period from 2004 to 2014, and panel model was used in this study. The results of this study showed that there is a positive and significant relationshipamong quality levels of financial information, including scores of timeliness, reliability, and final score of disclosure quality, and relevance of accounting information; while there is a negative and significant relationship between the conservatism of company's management and the relevance of accounting information. Moreover, the results of this study indicated that there is a negative and significant relationship among the mutual impactof the final score of financial information disclosure quality and the conservatism of company's management on the relevance of accounting information. Keywords: disclosure quality, conservatism, relevance of accounting information. JEL Classifications: C32; O13; O47